THE EFFECTS OF SGLT2 INHIBITORS IN CARDIOVASCULAR PROTECTION: A REVIEW OF MECHANISTIC INSIGHTS AND CLINICAL EVIDENCE - Daniel Sagan; Marta Góral; Rafał Siedlecki; Dominik Fidorowicz; Katarzyna Helena Sergiel; Emilia Torbacka; Aleksandra Irena Skuza; Magda Downar-Zapolska; Agnieszka Mikłaszewicz; Katarzyna Bednarczuk (International Journal of Innovative Technologies in Social Science, 2026)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors, or gliflozins, represent one of the most significant pharmacological breakthroughs in modern cardiovascular and renal medicine. Originally developed as glucose-lowering agents for type 2 diabetes, these medications have demonstrated profound, life-saving cardiovascular benefits in patients, regardless of their glycemic status. This shift from a "glucocentric" to an "organoprotective" paradigm is driven by a complex array of pleiotropic mechanisms that transcend simple osmotic diuresis.This work provides a comprehensive analysis of the multifaceted physiological pathways through which SGLT2 inhibitors exert their effects. Key mechanisms explored include the optimization of myocardial bioenergetics through ketone body utilization, the stabilization of ion exchange, the restoration of tubuloglomerular feedback, reduction of epicardial adipose tissue, microbiome management and improvement in cardiac muscle remodelling.This review evaluates the landmark clinical evidence from pivotal trials such as EMPA-REG, DAPA-HF, EMPEROR-Reduced, EMPEROR-Preserved, DELIVER, DAPA-MODA, DAPA-CKD, CREDENCE, EMPA-KIDNEY, DAPA-MI and EMPACT-MI; exploring the SGLT2i role in patients with heart failure and chronic kidney disease. These studies have established SGLT2 inhibitors as the first class of therapy to show consistent mortality and morbidity benefits across the entire spectrum of left ventricular ejection fraction. The work also addresses recent 2024 to 2025 data regarding early implementation in the post-myocardial infarction setting and the emerging role of the gut-kidney-heart axis in modulating systemic inflammation.Materials and Methods: The article was written based on scientific papers available on PubMed and Google Scholar.